Efficacy of Some Combined Conservative Methods in the Treatment of Carpal Tunnel Syndrome: A Randomized Controlled Clinical and Electrophysiological Trial - Tomris DUYMAZ; Dilşad SİNDEL and Nur KESİKTAŞ and Lütfiye MÜSLÜMANOĞLU (Archives of Rheumatology, 2012)
Objectives: In this study, we aimed to compare the efficacy of some conservative methods in combination with dexamethasone iontophoresis, ultrasound therapy or placebo iontophoresis (without dexamethasone) in the treatment of mild carpal tunnel syndrome (CTS). Patients and methods: Fifty-eight patients diagnosed with mild CTS confirmed by electromyography were included in the study. The subjects were divided randomly into three groups: (i) iontophoresis group-treated with dexamethasone iontophoresis (n=20); (ii) ultrasound group-treated with ultrasound (n=20), and (iii) placebo group-treated with placebo iontophoresis (n=18). All patients received one of these treatments in 15 sessions for three months in combination with physiotherapeutic procedures, such as tendon/nerve gliding exercises, night splinting and activity modifications. Wrist range of motion, muscle test, the Visual Analog Scale (VAS), handgrip test, pinch meter measurement, sensory testing with monofilaments, two-point discrimination test, Phalen’s, reverse Phalen’s, Tinnel’s and carpal compression test, the Health Assessment Questionnaire (HAQ), the Boston Questionnaire (BQ) and electrophysiological assessment were performed at baseline, at the end of therapies and at threemonths during follow-up. Statistical analysis was performed using SPSS software (version 10.0 for Windows). Results: Statistically significant improvements in the clinical status of all groups were observed at the end of the study (p≤0.05). Compared to ultrasound group and placebo group, more successful outcomes were seen in the iontophoresis group, resulting in statistically significant improvements in the pinch meter measurements, monofilament and two-point discrimination tests, and in BQ scores at three months during follow-up (p≤0.05). A statistically significant improvement was also recorded in the electrophysiological measurements in the iontophoresis group and ultrasound group (p≤0.05). Conclusion: Our study results suggest that dexamethasone iontophoresis administration combined with tendon gliding exercises, splint and activity modification is reliable and effective in the treatment of patients with mild CTS. However, further large-scale studies are required to confirm these findings.